Two Cases of Duodenal Somatostatinoma Associated with von Recklinghausen's Disease - Nomizu, Tadashi; Watanabe, Fumiaki; Yamaguchi, Yoshiko; Sakuma, Takeshi; Yamada, Mutsuo; Katagata, Naoto; Nihei, Mitsuhiro; Gonda, Kenzi (Nippon Shokaki Geka Gakkai zasshi, 2005)
We report two cases of duodenal somatostatinoma associated with von Recklinghausen's disease. Case 1 involved a 45-year-old man and case 2 a 67-year-old man, in whom cafe-aulait skin macules and multiple neurofibromas were noted over the entire body. They underwent pancreatoduodenectomy based on a diagnosis of duodenal carcinoid in the oral side of the papilla of Vater. Histologically, the duodenal tumors in these cases infiltrated the pancreatic head. A high-power view showed tumors to consist of small round cells with a solid or trabecular pattern and conspicuous psammoma bodies. Regional lymph nodes contained metastases. Immunohistochemical examination showed that tumor cells stained for somatostatin and chromogranin. In case 1, ultrastractual study demonstrated neuroendocrine secretory granules (300-400 nm in diameter) in cytoplasm. It is noted that somatostatinoma should be considered on differential diagnosis in patient with von Recklinghausen's disease accompanied with periampullary neoplasm.